A variable resolution approach for improved acquisition of hyperpolarized 13C metabolic MRI. Issue 6 (22nd July 2020) - Gordon, Jeremy W.; Autry, Adam W.; Tang, Shuyu; Graham, Jasmine Y.; Bok, Robert A.; Zhu, Xucheng; Villanueva‐Meyer, Javier E.; Li, Yan; Ohilger, Michael A.; Abraham, Maria Roselle; Xu, Duan; Vigneron, Daniel B.; et al.
Abstract : Purpose: To ameliorate tradeoffs between a fixed spatial resolution and signal‐to‐noise ratio (SNR) for hyperpolarized 13 C MRI. Methods: In MRI, SNR is proportional to voxel volume but retrospective downsampling or voxel averaging only improves SNR by the square root of voxel size. This can be exploited with a metabolite‐selective imaging approach that independently encodes each compound, yielding high‐resolution images for the injected substrate and coarser resolution images for downstream metabolites, while maintaining adequate SNR for each. To assess the efficacy of this approach, hyperpolarized [1‐ 13 C]pyruvate data were acquired in healthy Sprague‐Dawley rats ( n = 4) and in two healthy human subjects. Results: Compared with a constant resolution acquisition, variable‐resolution data sets showed improved detectability of metabolites in pre‐clinical renal studies with a 3.5‐fold, 8.7‐fold, and 6.0‐fold increase in SNR for lactate, alanine, and bicarbonate data, respectively. Variable‐resolution data sets from healthy human subjects showed cardiac structure and neuro‐vasculature in the higher resolution pyruvate images (6.0 × 6.0 mm 2 for cardiac and 7.5 × 7.5 mm 2 for brain) that would otherwise be missed due to partial‐volume effects and illustrates the level of detail that can be achieved with hyperpolarized substrates in a clinical setting. Conclusion: We developed a variable‐resolution strategy for hyperpolarized 13 C MRI using metabolite‐selective imaging and demonstrated that it mitigates tradeoffs between a fixed spatial resolution and SNR for hyperpolarized substrates, providing both high resolution pyruvate and coarse resolution metabolite data sets in a single exam. This technique shows promise to improve future studies by maximizing metabolite SNR while minimizing partial‐volume effects from the injected substrate.